Assessing adherence to standard guidelines in acute kidney injury (AKI) management: a compliance audit - Shadman Sakib Rahman; Kazi Subrina Nazneen; Sumaiya Kamal; Sm Rezwanuzzaman (Clinical Medicine)
Introduction: Acute kidney injury (AKI) is a significant global health concern, associated with high morbidity, mortality and healthcare costs.1 It is typically characterised by an abrupt rise in serum creatinine, a decrease in urine output, or both.2 Although many aetiologies of AKI can lead to severe outcomes, some forms are reversible, and a thorough understanding of the underlying pathology is crucial for guiding treatment strategies and prognosis.3 This retrospective audit evaluated adherence to both national (National Institute of Health and Care Excellence (NICE) NG148) and local Trust guidelines for AKI management, aiming to identify strengths and critical deficits, and propose targeted interventions for enhanced clinical outcomes.4,5 Materials and Methods: A total of 154 adult inpatients were identified with AKI from August to October 2024 through electronic patient records (EPRs), Sectra PACS and iLab systems. Compliance was assessed focusing on key metrics, such as AKI diagnosis documentation, aetiological investigations, fluid balance monitoring, medication review and specialist referrals. This approach ensured a comprehensive appraisal of compliance with evidence-based standards, while leveraging real-time patient data to reinforce the quality of research evidence. Results and Discussion: The results revealed that 85% of patients had an AKI diagnosis accurately documented, 86% underwent daily renal function testing and 85% received senior clinical review within 12 h of admission, reflecting timely initial recognition (Fig 1). Despite these strengths, aetiological factors were documented in only 50% of cases, suggesting a critical gap in diagnostic precision. Although intravenous fluid therapy was administered in most instances, fluid balance monitoring was suboptimal, with over half of the cohort lacking comprehensive intake–output charts. Furthermore, medication reviews were conducted in 73% of cases, yet inappropriate continuation of nephrotoxic agents was identified in several instances. Notably, only 39% of eligible patients received appropriate nephrology referrals, potentially jeopardising opportunities for specialist intervention (Fig 2). Conclusion: This audit highlights the need for a comprehensive improvement strategy, emphasising enhanced clinical education, integrated decision-support tools, and regular audits to ensure adherence to evidence-based guidelines. Standardising documentation and strengthening protocol compliance will help reduce preventable complications and improve accurate etiological identification. The work aims to streamline care pathways, enabling timely interventions that enhance patient safety and lessen the burden of AKI on healthcare resources. The audit is supported by a robust framework, data collection and diverse patient profiles, ensuring broad applicability. Its clinical relevance is reflected in strategies focused on medication stewardship, fluid balance management and specialist referrals. Ongoing departmental teaching, real-time clinical prompts and effective handovers drive continuous improvement and ensure adherence to best practices. These measures will improve clinical efficiency and patient care. Future evaluations should include patient-reported outcomes and cost-effectiveness analyses to refine strategies and align AKI care with national and international standards, ensuring sustained improvements. Regular departmental teaching, poster presentations and follow-up audits every 3–6 months are part of the plan–do–study–act (PDSA) cycle for continuous quality enhancement.